Pseudo-MOSFET transient behavior: Experiments, model, substrate and temperature effect. (December 2021) - Zhang, X.; Liu, F.Y.; Li, B.; Li, B.H.; Luo, J.J.; Han, Z.S.; Arsalan, M.; Wan, J.; Cristoloveanu, S.
Abstract: A theoretical model is proposed to characterize the transient operation of Pseudo-MOSFET under gate pulses by considering the substrate effect. The analysis provides Zerbst-like expression of drain current with substrate biased in deep-depletion state. The model can be used for the extraction of carrier lifetime with process parameter variations. The dependence of temperature on carrier lifetime was also modeled by including the temperature-dependent parameters (carrier concentration and effective mobility). TCAD simulations and experiments validate our model with the temperature ranging from 300 K to 370 K.